TOTAL ATELEKTAZİ YAPMIŞ AKCİĞER KANSERLİ OLGULARDA EKSTERNAL RADYOTERAPİNİN PALYATİF ETKİSİNİN RETROSPEKTİF OLARAK DEĞERLENDİRİLMESİ - ERDOĞAN KOÇAK, Mihriban; ÖNER DİNÇBAŞ, Fazilet and KOCA, Sedat (Cerrahpaşa Medical Journal, 2014)
Background and Design.- We evaluated the effect of radiation therapy in 27 patients with total atelectasis with lung cancer, between January 1980 and December 1996. The mean age of the patients was 56 years (31-87) of whom 26 were males. The patients were treated by primary radiation therapy, with doses ranging from 3000 to 6600 cGy. Initial symptoms included dyspnea in 24 (%88.8), cough in 22 (%81.4), hemoptysis in 5 (%18.5) and pain in 11 (%40.7) patients. The response of atelectasis to radiation therapy was established on the basis of follow–up chest roentgenograms. Follow-up was 1 to 24 months (median 6 months) Results.- Tweenty-seven patients with obstructive atelectasis were treated with external radiation therapy. Subjective response was achieved in %65 (17) of cases, objective response was %74 (20) of the cases. Dyspnea improved in %58.3, cough in % 54.3, hemoptysis in %80, pain in %54.5 of the patients. Twelve of 20 patients (%60), who had receive objective responses were treated with doses ranging from 5000-6600. Conclusion.- Radiotherapy is a feasible treatment modality of total atelectasis developed by means of lung cancer.